Levothyroxine use and thyroid gland volumes in children with autoimmune thyroiditis: a systematic review and meta-analysis - Annang Giri Moelyo; Indah Suci Widyahening; Bambang Tridjaja (Paediatrica Indonesiana, 2019)
Background Autoimmune thyroiditis may manifest as overt hypothyroidism, subclinical hypothyroidism, euthyroidism, or hyperthyroidism in children. Although there is no consensus on treating euthyroidism and autoimmune thyroiditis in children, some studies have demonstrated the efficacy of levothyroxine in reducing thyroid volume, improving thyroid function, and stabilizing the immunological process. Objective To determine the effect of levothyroxine on thyroid gland volume changes, thyroid function, and thyroid antibodies in euthyroid children with autoimmune thyroiditis. Methods We performed a literature search of electronic databases (the Cochrane Library, MEDLINE, EBSCO, ProQuest, clinicaltrials.gov, and other sources, as well as a non-electronic search (searching journals and conference proceedings by hand) to identify studies of euthyroid children with autoimmune thyroiditis published by August 2018. Only English-language articles were included in the search (electronic and non-electronic). Randomized controlled trials that compared levothyroxine with a control (placebo or no treatment) in euthyroid children with autoimmune thyroiditis were selected. The outcome measures were thyroid volume changes, thyroid function, and thyroid antibody levels in euthyroid children with autoimmune thyroiditis. Two authors independently extracted the data, assessed the risk of bias, and analyzed the pooled data from the included studies using a random effects model. The same authors performed a sensitivity analysis. Results We identified 57 studies. Of these, three studies, involving 97 subjects (51 subjects in an intervention group and 46 subjects in the control group) were selected for inclusion in a systematic review/meta-analysis. The meta-analysis revealed a significant difference in mean thyroid volume changes between the two groups (-1.10 SDs; 95%CI -1.56 to -0.64; P<0.0001; I2=6%). The mean difference in the thyroid-stimulating hormone (TSH) change of the two groups was -1.82 mU/L (95%CI -3.52 to -0.11; I2=87%; P=0.04). The standardized mean difference in free thyroxine (fT4) change of the two groups was 0.82 pmol/L (95%CI -1.14 to 2.78; I2=89%; P=0.41). Conclusion In euthyroid children with autoimmune thyroiditis, levothyroxine treatment reduces the thyroid volume better. The TSH level change in the intervention group is better than those in the control group. Levothyroxine treatment did not significantly improve free T4.